Production of adsorbents by pyrolysis of paper mill sludge and application on the removal of citalopram from water - Calisto, Vânia
This work describes the production of alternative adsorbents from industrial residues and their application for the removal of a highly consumed antidepressant (citalopram) from water. The adsorbents were produced by pyrolysis of both primary and biological paper mill sludge at different temperatures and residence times. The original sludge and the produced chars were fully characterized by elemental and proximate analyses, total organic carbon, specific surface area (BET), N2 isotherms, FTIR, 13C and 1H solid state NMR and SEM. Batch kinetic and equilibrium experiments were carried out to describe the adsorption of citalopram onto the produced materials. The fastest kinetics and the highest adsorption capacity were obtained using primary sludge pyrolysed at 800??C during 150min. The use of pyrolysed paper mill sludge for the remediation of contaminated waters might constitute an interesting application for the valorization of those wastes.